Cognitive Agent-based Computing-I A Unified Framework for Modeling Complex Adaptive Systems using Agent-based & Complex Network-based Methods - Niazi, Muaz A.; Hussain, Amir.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2013)
Complex Systems are made up of numerous interacting sub-components. Non-linear interactions of these components or agents give rise to emergent behavior observable at the global scale. Agent-based modeling and simulation is a proven paradigm which has previously been used for effective computational modeling of complex systems in various domains. Because of its popular use across different scientific domains, research in agent-based modeling has primarily been vertical in nature. The goal of this book is to provide a single hands-on guide to developing cognitive agent-based models for the exploration of emergence across various types of complex systems. We present practical ideas and examples for researchers and practitioners for the building of agent-based models using a horizontal approach - applications are demonstrated in a number of exciting domains as diverse as wireless sensors networks, peer-to-peer networks, complex social systems, research networks and epidemiological HIV.
Keywords: Medicine; Neurosciences; Computer science; Mathematics; Consciousness; Biomedicine; Neurosciences; Computer Science, general; Mathematics, general; Cognitive Psychology; Biophysics and Biological Physics